Nanoformulations for the Delivery of Dietary Anthocyanins for the Prevention and Treatment of Diabetes Mellitus and Its Complications - Ana R. Nunes; Elisabete C. Costa; Gilberto Alves; Luís R. Silva (Pharmaceuticals, 2023)
Diabetes mellitus (DM) is a metabolic disease characterized by abnormal blood glucose levels-hyperglycemia, caused by a lack of insulin secretion, impaired insulin action, or a combination of both. The incidence of DM is increasing, resulting in billions of dollars in annual healthcare costs worldwide. Current therapeutics aim to control hyperglycemia and reduce blood glucose levels to normal. However, most modern drugs have numerous side effects, some of which cause severe kidney and liver problems. On the other hand, natural compounds rich in anthocyanidins (cyanidin, delphinidin, malvidin, pelargonidin, peonidin, and petunidin) have also been used for the prevention and treatment of DM. However, lack of standardization, poor stability, unpleasant taste, and decreased absorption leading to low bioavailability have hindered the application of anthocyanins as therapeutics. Therefore, nanotechnology has been used for more successful delivery of these bioactive compounds. This review summarizes the potential of anthocyanins for the prevention and treatment of DM and its complications, as well as the strategies and advances in the delivery of anthocyanins using nanoformulations.